1997
DOI: 10.1016/s0022-5223(97)70187-9
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation after cardiac operations in neonates and young infants

Abstract: Early extubation can be accomplished safely in many neonates and young infants undergoing cardiac operations for repair of congenital heart defects and can shorten hospital stay and reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
105
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 18 publications
8
105
0
2
Order By: Relevance
“…For each month of the age risk for prolonged ventilation is decreased for 4%. Significant pulmonary hypertension was considered important risk factor of prolonged mechanical ventilation (11)(12)(13)(14), that was confirmed by this study.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…For each month of the age risk for prolonged ventilation is decreased for 4%. Significant pulmonary hypertension was considered important risk factor of prolonged mechanical ventilation (11)(12)(13)(14), that was confirmed by this study.…”
supporting
confidence: 81%
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 72%
“…Evidence to prove feasibility, safety, and costs associated with fast tracking in CHD surgery is mostly limited to single-center experiences. [3][4][5][6] No study to date has compared a cohort of infants and children undergoing surgery for CHD using an integrated fast-tracking strategy with a contemporaneous control cohort.…”
mentioning
confidence: 99%
“…3 Interest has therefore been shifted from reducing operative mortality to facilitating quicker recovery and reducing intensive care unit (ICU) stay and hospital stay by applying an early extubation policy and/or fast-track cardiac surgery pathways. [4][5][6] However, stress response to cardiopulmonary bypass (CPB) is much greater in neonates than in older children, 7 and postoperative recovery in neonates can therefore often be compromised by CPB-induced organ dysfunction.Modified ultrafiltration (MUF), which was introduced by Naik et al in 1991, has become an essential perfusion strategy to minimize CPB-induced adverse effects in pediatric patients undergoing open-heart surgery. 8 A substantial body of evidence showed that MUF improves cardiac, pulmonary and cerebral functions 9-12 and decreases postoperative bleeding and blood transfusion requirement 13 by reduction of body water accumulation, reversal of hemodilution, and modulation of systemic inflammatory mediators.…”
mentioning
confidence: 99%
“…3 Interest has therefore been shifted from reducing operative mortality to facilitating quicker recovery and reducing intensive care unit (ICU) stay and hospital stay by applying an early extubation policy and/or fast-track cardiac surgery pathways. [4][5][6] However, stress response to cardiopulmonary bypass (CPB) is much greater in neonates than in older children, 7 and postoperative recovery in neonates can therefore often be compromised by CPB-induced organ dysfunction.…”
mentioning
confidence: 99%